Elementary School Teachers Performance: How The Role of Transformational Leadership, Competency, and Self-Efficacy? - Muliati, Lisdewi; Asbari, Masduki; Nadeak, Multi; Novitasari, Dewiana; Purwanto, Agus (IJOSMAS, 2022)
This study aims to analyze the relationship between transformational leadership, competency, and self-efficacy on the performance of elementary school teachers. This research method is quantitative with data processing tools using SPSS software. Data were obtained through the distribution of online questionnaires to 210 elementary school teachers in Tangerang who were selected using the simple random sampling method. Based on the data analysis, it can be concluded that transformational leadership has a positive effect on teachers performance, competency has a positive effect on teachers performance, self-efficacy has a positive effect on teachers performance, and transformational leadership, competency, and self-efficacy simultaneously have a positive and significant effect on teachers performance.